Situation of liver fl uke and cholangiocarcinoma among patients and risk groups of liver fl uke in Maha Sarakham Province, Thailand - Chaveepojnkamjorn, Wisit; Pichainarong, Natchaporn; Wichaiyo, Woragon (Food Agricultural Sciences and Technology, 2016)
The objective of this point cross-sectional study was to explore the situation of liver fl uke, cholangiocarcinoma, preventive behaviors and other health-risk behaviors among patients and risk groups of liver fl uke at Nadoon Municipality, Nadoon District, Maha Sarakham Province, Thailand. A simple random sampling technique was used for selecting 1,148 villagers from 10 villages of Nadoon District, which was carried out from January 2014 to February 2014. All subjects were interviewed. Results showed that the incidence rate of liver fl uke was 2.3% and the cholangiocarcinoma incidence rate was 2.8%. The subjects were female (53.2%), married (81.3%) and older (40-60 years) (68.3%). Most of them had a primary school education level (69.9%), were agriculturists (68.6%), families had 3-4 persons (41.9%) and had monthly family incomes lower than 5,000 Baht (72.9%). The largest source of information about liver fl uke was 80.7% from public health personnel and 77.5% from television/radio. Raw fi sh dishes were among the favorite foods with a medium period of intake of 34.0 years, which comprise of more than 50% intake of bonnelville raw fi sh (jaew bong), orange little fi sh (som pla noi), food with raw pickled fi sh, raw fi sh consumed (mam) and raw pickled fi sh (pla jom), (range 53.7%-81.8%). The rest consumed it in the range from 9.2%-43.4%, such as raw fermented fi sh (som pla), minced fermented fi sh with chili paste and raw fi sh with spiced salad (koi pla). Stool exams were performed for the detection of liver fl ukes (27.4%). Liver fl uke anthelmintic drug intake was by 31.3%, who obtained it manly from health services as 42.1%. Although many control programs have been used among them, the incidence of reinfection remained the same. Precise and regular main raw fi sh dishes, drug intake, hygienic defecation data directly from public health personnel and television/ radio should be strong concerned with suffi cient diagnosis and treatment.